Menumbuhkan Kesadaran Akan Pentingnya Pendidikan Anak Usia Dini melalui Motivasi Belajar: Pendekatan Partisipatif dalam Pemberdayaan Komunitas - Resna Hegi Putra; Toni Efriyandika; Yuni Pantiwati; Iin Hindun; Abdulkadir Raharjdjanto (WISE Pendidikan Indonesia, 2025)
This study aims to strengthen community awareness of the importance of early childhood education through a participatory learning motivation program facilitated by university students in Sukaraja Village, West Lampung, Indonesia. Using a descriptive qualitative design with a participatory approach, the research involved 15 children aged 4-6 years and 10 parents selected through purposive sampling. Data were collected through semi-structured interviews, field observations, and documentation, then analyzed using Miles and Huberman’s interactive model supported by triangulation to ensure validity. The findings demonstrate that participatory learning activities significantly enhanced children’s enthusiasm, parental involvement, and collective community awareness toward early education. The program successfully integrated intrinsic and extrinsic motivation by combining play-based methods, peer interaction, and contextual learning environments. Furthermore, two informal learning groups emerged as a sustainable community-driven initiative after the program ended. The study contributes a novel participatory motivation framework that integrates educational awareness, family engagement, and community empowerment to promote inclusive early education in rural contexts.